تحسين أداء بروتوكول AODV في شبكات الحساسات اللاسلكية المستخدمة في الكشف عن حرائق الغابات (Latakia University Journal -Engineering Sciences Series, 2018)
تتنوع البروتوكولات المستخدمة في شبكات الحسّاسات اللاسلكية منها ما هواستباقي(proactive) حيث تحتفظ العقد دائماً بمسار توجيهي للهدف، ومنها ماهو على الطلب(on demand) أي أن العقدة تحصل على المسار فقط عندما تحتاج للإرسال, ومنها ما هو هجين بين النمطين السابقين (Hybrid) وبحسب التطبيق يتم اختيار بروتوكول معين تحت هذه الأنماط.سنقوم في هذا البحث بإجراء تعديل على بروتوكول التوجيه عند الطلبAODVبحيث يقوم بنقل بارامترات إضافية هامّة لموضوع البحث، والتي تساهم بدورها في تحسين أداء الشبكة ككل، إضافةً إلى تعديل آلية اختيار المسار بحيث يكون المسار مكوناً من العقد ذات الطاقة المرتفعة نسبياً واستبعاد العقد ذات الطاقة المنخفضة من عملية تشكيل المسار.تمّت دراسة تأثير ذلك التعديل على الشبكة من حيث التأخير، والإنتاجيّة وقد توصلت الدراسة إلى مجموعة من النتائج والتوصيات إذ تحسنت الإنتاجية وانخفض تأخير نهاية-نهاية، ومن المناسب استخدام هذا البروتوكول المعدّل في الشبكات ذات الإزدحام المنخفض.Protocols used in wireless sensors` networks varies in types, some of them are “proactive”; where the node always keeps a guiding path ,the other type is “ on demand protocols” where the node gets its path only when it needs to send packets to other node, and “hybrid” between the last two types. Application wise, a certain protocol has been examined according to these threetypes. The on demand routing protocol AODV, is the one which we will adopt in this research and it aims to amend the protocol in order to transmit extra useful parameters that are strongly attached to the scope of this researchand subsequently they contribute to improve the performance of the whole network, in addition to modify the path establishment mechanism, where the path is formed by nodes of relatively high power , and by eliminating nodes of low power . Influence of the above had been studied upon the network in terms of time - delay and throughput.The study reaches a set of suggestions and conclusions , in the results of simulation, the modulated protocol proof that it is better than the original protocol in throughput and end to end delay, and this modulated protocol is suitable to use in low jam networks.